Implementação da técnica de software pipelining na rede em chip IPNoSyS - Medeiros, Aparecida Lopes de (2014)
Alongside the advances of technologies, embedded systems are increasingly present in our everyday. Due to increasing demand for functionalities, many tasks are split among processors, requiring more efficient communication architectures, such as networks on chip (NoC). The NoCs are structures that have routers with channel point-to-point interconnect the cores of system on chip (SoC), providing communication. There are several networks on chip in the literature, each with its specific characteristics. Among these, for this work was chosen the Integrated Processing System NoC (IPNoSyS) as a network on chip with different characteristics compared to general NoCs, because their routing components also accumulate processing function, ie, units have functional able to execute instructions. With this new model, packets are processed and routed by the router architecture. This work aims at improving the performance of applications that have repetition, since these applications spend more time in their execution, which occurs through repeated execution of his instructions. Thus, this work proposes to optimize the runtime of these structures by employing a technique of instruction-level parallelism, in order to optimize the resources offered by the architecture. The applications are tested on a dedicated simulator and the results compared with the original version of the architecture, which in turn, implements only packet level parallelism